Bidirectional Cavopulmonary Shunt Surgery of Tetralogy of Fallotwith Situs Inversus and Levocardia in 20-Month-Old Boy : A Rare Case Report - Suprayitno Wardoyo; Dhama Shinta Susanti; William Makdinata; Albert Jeo (Syntax Corporation Indonesia, 2023)
Tetralogy of Fallot (TOF) is a relatively common cyanotic congenital heart disease, characterized by four distinct defects. Although TOF is a common condition, its association with situs inversus and levocardia is rare, presenting diagnostic and treatment challenges. This case report discusses a 20-month-old boy with TOF, situs inversus, and levocardia. Initially planned for total surgical correction, intraoperative anatomical complexities led to the decision to perform a bidirectional cavopulmonary shunt surgery. This procedure aimed to enhance oxygen saturation and reduce the volume load on the right ventricle, due to severe pulmonary stenosis and perimembranous ventricular septal defect. The bidirectional cavopulmonary shunt serves to improve systemic arterial oxygen without increasing ventricular work or pulmonary vascular resistance. This case highlights the significance of individualized treatment approaches when TOF is associated with complex anatomical variations